Parents’ Lifestyle and Children Upbringing in Ede, Osun State - Oke , Adeola Idowu (Corpus Intellectual, 2024)
Parents' negligence and an unhealthy lifestyle of some parents have contributed negatively to the upbringing of children in our society. Also, the parent's carefree attitude harms these children's growth and development. This study employed a descriptive survey method, and through an effective research instrument, data were collected from two hundred population of teens, youths and parents of the Redeemed College of Missions and the Redeemed Christian Church of God, Pentecost Model Parish, Osun Province 9, Ede, Osun State. Percentage on a group basis was used to analyze the collected data. The findings revealed that children do not try to imitate whatever they find their parents doing because they already suffer emotional problems due to the lack of peace between them and their parents. The findings also showed that parents should live peacefully with one another to be role models for their children. Also, it was revealed that though parents pay attention to their children's behaviours, attention, at times, is inadequate. Most times, these parents are completely ignorant of their children's private life experiences, and as a result, they do not know their best friends and care less about it. Based on the findings of this study, the study concluded that parents should engage and spend quality time with their children so that they will know their private life experiences via effective communication and intimacy which are key to the proper upbringing of their children. The Researcher then recommended that parents should expose their children to moral, spiritual, and sexual education.